2013
DOI: 10.1002/2013jd020908
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic variability of the Asian monsoon anticyclone observed in potential vorticity and correlations with tracer distributions

Abstract: [1] The Asian summer monsoon is associated with strong upward transport of tropospheric source gases and isolation of air within the upper tropospheric anticyclone, with a high degree of dynamical variability. Here we study the anticyclone in terms of potential vorticity (PV) as derived from reanalysis data. The strength of the anticyclone, as measured by low PV area, varies on subseasonal time scales (periods of 30-40 days), driven by variability in convection. The convective forcing of low PV areas is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
176
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(206 citation statements)
references
References 32 publications
(37 reference statements)
28
176
0
Order By: Relevance
“…Our findings show that the most important mechanism for long-range transport of air masses from the Asian monsoon anticyclone to the extratropical lower stratosphere is eastward-migrating anticyclones breaking off from the main anticyclone a few times each summer (Dethof et al, 1999;Popovic and Plumb, 2001;Garny and Randel, 2013;Vogel et al, 2014;Ploeger et al, 2015) and filaments separated on the northeastern flank of the anticyclone. In our case study for the eddy-shedding event on 20 September 2012, enhanced contributions of young air masses (younger than 5 months) are found within the separated anticyclone and filaments within the upper troposphere.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our findings show that the most important mechanism for long-range transport of air masses from the Asian monsoon anticyclone to the extratropical lower stratosphere is eastward-migrating anticyclones breaking off from the main anticyclone a few times each summer (Dethof et al, 1999;Popovic and Plumb, 2001;Garny and Randel, 2013;Vogel et al, 2014;Ploeger et al, 2015) and filaments separated on the northeastern flank of the anticyclone. In our case study for the eddy-shedding event on 20 September 2012, enhanced contributions of young air masses (younger than 5 months) are found within the separated anticyclone and filaments within the upper troposphere.…”
Section: Discussionmentioning
confidence: 76%
“…In particular, eastward-migrating anticyclones break off from the main anticyclone a few times each summer (Dethof et al, 1999;Hsu and Plumb, 2001;Popovic and Plumb, 2001;Garny and Randel, 2013;Vogel et al, 2014;Ungermann et al, 2016) and have the potential to carry air with high amounts of tropospheric trace gases from the Asian monsoon anticyclone to middle and high latitudes of the Northern Hemisphere. These young air masses can be transported into the extratropical lower stratosphere where they are eventually mixed irreversibly with the surrounding aged stratospheric air (Dethof et al, 1999;Garny and Randel, 2013;Vogel et al, 2014), thus affecting the chemical and radiative balance of the extratropical lower stratosphere. However, the exact transport mechanisms of young air masses from the troposphere, including air originating within the Asian monsoon anticyclone into the lower stratosphere, are yet to be identified and quantified.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that trace gas confinement within the monsoon anticyclone core can be best described by potential vorticity (PV) contours (Garny and Randel, 2013), and that the anticyclone core can be clearly distinguished from the surrounding atmosphere in a layer around 380 K potential temperature (Ploeger et al, 2015;Ungermann et al, 2016). We therefore apply the method of Ploeger et al (2015) to determine the PV value related to the anticyclone border from the maximum PV gradient on every day during (boreal) summers 2010-2013 at the 370 and 380 K potential temperature surfaces (see Appendix for further details, and the Supplement for the data).…”
Section: Methodsmentioning
confidence: 99%
“…approximately the whole upper troposphere and lower stratosphere (UTLS) region. Despite the closed anticyclonic flow often shown in climatological analysis, the circulation system exhibits strong variability in strength and location (Hsu and Plumb, 2000;Popovic and Plumb, 2001;Garny and Randel, 2013;Ploeger et al, 2015;Vogel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%